2020
DOI: 10.1002/hep.31158
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Physical Activity and Sedentary Behavior Are Independent Predictors of Nonalcoholic Fatty Liver Disease

Abstract: Background and Aims In general, physical activity (PA) and nonalcoholic fatty liver disease (NAFLD) have an inverse association. However, studies assessing the impact of the widely accepted Physical Activity Guidelines for Americans (PA Guidelines) on NAFLD are lacking. Approach and Results We performed a serial, cross‐sectional analysis among adults by using the 2007‐2016 US National Health and Nutrition Examination Survey. NAFLD and advanced fibrosis were defined by using various noninvasive panels. A PA que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 39 publications
7
84
0
2
Order By: Relevance
“…We also identified lifestyle factors were associated with hepatic steatosis and fibrosis. Compared with previous studies, 16,26,27 the current study compares lifestyle habits of real‐world NAFLD patients from different countries and regions. While the lifestyle habits vary across regions, inadequate PA was observed consistently in all participating sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also identified lifestyle factors were associated with hepatic steatosis and fibrosis. Compared with previous studies, 16,26,27 the current study compares lifestyle habits of real‐world NAFLD patients from different countries and regions. While the lifestyle habits vary across regions, inadequate PA was observed consistently in all participating sites.…”
Section: Discussionmentioning
confidence: 99%
“…factors were associated with hepatic steatosis and fibrosis. Compared with previous studies, 16,26,27 the current study compares lifestyle habits of real-world NAFLD patients from different countries and regions.…”
Section: Ta B L E 5 Lifestyle Habits Associated With the Severity Of mentioning
confidence: 99%
“…Thus, NASH is more closely related to 'metabolic obesity' than to body weight [6]. Risk factors for NASH include excessive intake of calorie-dense food, reduced physical activity and exercise, and genetic susceptibility [7].…”
Section: Pathogenic Drivers Of Disease Progression and Mortality In Nashmentioning
confidence: 99%
“…Further work has shown that more than 3 cups of coffee per day is associated with a lower risk of CVD and risk of death post-myocardial infarction. (20, 34- 36) Inadequate physical activity or sedentary lifestyle is a risk factor associated with NAFLD and CVD (37)(38)(39). A recent US population-based study showed that the prevalence of meeting the physical activity guidelines (≥150 minutes/week) was markedly higher in subjects without NAFLD than those with NAFLD, which was mostly attributable to the higher prevalence of leisure-time physical activity in those without NAFLD (37).…”
mentioning
confidence: 99%
“…(20, 34- 36) Inadequate physical activity or sedentary lifestyle is a risk factor associated with NAFLD and CVD (37)(38)(39). A recent US population-based study showed that the prevalence of meeting the physical activity guidelines (≥150 minutes/week) was markedly higher in subjects without NAFLD than those with NAFLD, which was mostly attributable to the higher prevalence of leisure-time physical activity in those without NAFLD (37). Physical activity is a proven therapeutic strategy to improve liver fat content, insulin resistance, and decrease the risk of CVD.…”
mentioning
confidence: 99%